If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 76 + 2x = 228 Solving 76 + 2x = 228 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-76' to each side of the equation. 76 + -76 + 2x = 228 + -76 Combine like terms: 76 + -76 = 0 0 + 2x = 228 + -76 2x = 228 + -76 Combine like terms: 228 + -76 = 152 2x = 152 Divide each side by '2'. x = 76 Simplifying x = 76
| 3x^2-4+1=0 | | P=rq+a | | 10-5x=2x+11 | | X-4=-5x+8 | | 23=6x-15 | | (16x^2)-40=0 | | 4s+9t=43 | | 36-(3c+4)=3(c+7)+c | | 2(x-4)=3x+11 | | W=mb-r | | 4x-3(2-3x)=4(x-4)-17 | | 5.05t=1.48t-3.57 | | -7/2r=-63/8 | | 2x+2y+3x+6y= | | 2(x-4)=2x+11 | | z+8=12-z | | Z=a-b+c | | 0=56x^2-72x+144 | | 16x^2-4x+252=0 | | 3/17=x/7 | | x=3-14 | | -2x=-54 | | (V+3)2=28 | | 4y-40=8y | | ((5Y^6)/(3Y^4))^(1/5) | | 4-y+2=-4 | | 17x^2+11x-6=0 | | 2(q-29)=1/2(4-8q) | | 3n^2=-12n-7 | | v+3squared=28 | | 5x-7/4=1/3 | | 6x+3=8x-17 |